THE IMPACT OF COVID-19 PANDEMIC ON THE COST STRUCTURE AND PROFITABILITY OF TEMPE AGROINDUSTRY IN THE CITY OF BANDAR LAMPUNG - Firdasari, Firdasari; Haryono, Dwi; Saleh, Yuliana; Sari, Dewi Mulia (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
The Covid-19 pandemic in 2020 affected every aspect of life, including the slowdown of economic growth. However, there are sectors that have proven to be resilient in the midst of the pandemic, namely the agricultural sector and the processing industry.  This research aims to determine the impact of the Covid-19 pandemic on the cost structure and profits of the tempe agro-industry in Bandar Lampung.  This research involved 32 tempe agro-industries using quota sampling technique.  The data analysis methods used include cost structure analysis, profit analysis, and paired sample t-tests.  The research results show that the cost structure and profits of the tempe agro-industry in Bandar Lampung are influenced by the Covid-19 pandemic.  The largest and most significant cost structure difference lies in the main raw material, which is soybeans, with a percentage of 62.99 percent before the pandemic and 66.46 percent after the pandemic.  Meanwhile, the total costs have significantly increased, rising by 8.59 percent each month following the occurrence of the Covid-19 pandemic.  In addition, the pandemic also significantly affected the profit structure of the tempe agro-industry, reducing income by 11.80 percent and profits by 40.15 percent. Keywords: Agroindustri, Pandemi Covid-19, Tempe, UMKM